Public awareness of tetralogy of Fallot after Jimmy Kimmel Live! television episode: A cross-sectional analysis. (17th August 2020) - Henrion, Marc; Greiner, Benjamin; Lee, Abraham; Checketts, Jake; Hartwell, Micah
Abstract: Background: Persons with rare disorders, such as tetralogy of Fallot, often feel socially isolated due to poor public awareness of the disorder. On 1 May 2017, Jimmy Kimmel aired a segment on Jimmy Kimmel Live! highlighting the impact of tetralogy of Fallot on his son and how the public can learn more about the disorder. Methods: We tracked public interest in tetralogy of Fallot using Google Trends and Twitter after the episode and constructed an autoregressive integrated moving average algorithm to calculate search volumes had Kimmel not aired the episode. Results: Google searches and the number of Tweets for tetralogy of Fallot increased by 3063.27% and 4672.62%, respectively, above expected. Conclusions: Our findings indicate that television talk shows may represent strong outlets for increasing public awareness of rare disorders.